Construction and Validation of Emotional Agility Measurement Tools : Measuring One'S Emotional Agility - Kamilah, Hana; Hanifah, Hanifah (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
Mental health includes one’s ability to adjust themselves with the daily stres they experience. On stresful event, there’s always highly emotional condition attached, therefore the ability to regulate emotions becomes vital. Emotional Agility is one’s ability to face emotions, thoughts loosely and move past them to help change or retain behaviors in line with goal and values . In Indonesia, research regarding Emotional Agility and it’s measurement hasn’t been explored much. The instrument are designed based on Emotional Agility theory–Susan David and being tried out to 112 respondents (young adult individuals). The validity test being used pertains to Construct Validity, using model testing Confirmatory Factor Analysis. Reliability test are done using Alpha Cronbach technique. Based on the try out, an instrument of Emotional Agility in Indonesian Version is produced consisting 49 items (p-value=1.00, RMSEA=0.00, CFI=0.97, NFI=0.97, IFI=0.97 and reliability coefficient of 0.860).